The Improvement if Integrated Thematic Learning Process by Using Discovery Learning Model in Class IV Elementary School - Maistika Ratih (International Journal of Educational Dynamics, 2019)
Abstract: The background of the research is that the teachers in the integrated thematic learning process are not maximal and tend to use the lecture method. The research objective was to describe the improvement of an integrated thematic learning process with the Discovery Learning model in theme 4 in class IV SDN 14 Sungai Sirah. This research is a classroom action research, using qualitative and quantitative approaches. Conducted in two cycles, each cycle includes four stages, namely planning, implementation, observation, reflection. The research subjects were teachers and fourth grade students in the amount of 30 students. The technique used is data collection with research instruments, namely observation and documentation. The results of the study showed: a) RPP cycle I (meeting 1) 68.5% (B), cycle I (meeting 2) 79.7% (B), and cycle II 89.3% (AB), b) implementation on aspects of teacher cycle I ( meeting 1) 71.5% (C), cycle I (meeting 2) 77.9% (good), and cycle II 85.8% (good), c) implementation on aspects of student cycle I (meeting 1) 67.8% (C), cycle I (meeting 2) 80.5% (B), and cycle II 88.9% (B). Based on the results of research with the Discovery Learning model can improve the thematic learning process